Analisis Efektivitas Peraturan Hukum terhadap Tindak Pidana Kekerasan Seksual pada Anak (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Children are a vulnerable group frequently subjected to sexual violence, whether in the form of physical abuse, psychological harm, or sexual exploitation such as pornography and prostitution. This study aims to analyze the effectiveness of legal regulations in providing protection for children against sexual violence crimes. The research is motivated by the high rate of sexual violence against children in Indonesia and the suboptimal implementation of existing regulations in ensuring justice and safety for victims. The research method used is a normative juridical approach with descriptive-qualitative analysis through the study of national laws, international conventions, and relevant literature. The findings reveal that although Indonesia has enacted regulations such as Law Number 35 of 2014 and ratified the Convention on the Rights of the Child, their implementation still faces challenges including social stigma, insufficient legal support for children, and bureaucratic delays. This study concludes that legal protection for child victims of sexual violence must be strengthened through regulatory reform, institutional capacity building, and synergy between the state, society, and local communities.